A Call for Paradigm Shift of English Language Teaching in Thailand to Teaching Global Englishes - (ภาวัต วิสุทฺเธสโก - แสวงดี), พระอุดมธีรคุณ (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This article aims at providing the view and changes of the trend in English Language Teaching (ELT) in Thailand including challenges that Thailand is supposed to face and possible solution which is beneficial for providing some though in policy setting and practical application of ELT in Thailand.